2010
DOI: 10.1007/s11136-010-9662-0
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring symptoms at home: what methods would cancer patients be comfortable using?

Abstract: Purpose This study aimed to determine which methods of remote symptom assessment cancer outpatients would be comfortable using, including those involving information technology, and whether this varied with age and gender.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 17 publications
0
8
0
1
Order By: Relevance
“…Earlier studies have also shown how factors related to the systems structure and login procedures affect use [16,55]. In addition, it has been emphasized that a clear and shared understanding of the features available in the communication service is essential and that providing information at the time of enrollment can increase use of the system [22,56]. Other studies have found that lack of training is a barrier to use of email by patients with cancer [57] and that many people will not be able to make use of eHealth technologies without at the same time being offered support in how to use the services [58].…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies have also shown how factors related to the systems structure and login procedures affect use [16,55]. In addition, it has been emphasized that a clear and shared understanding of the features available in the communication service is essential and that providing information at the time of enrollment can increase use of the system [22,56]. Other studies have found that lack of training is a barrier to use of email by patients with cancer [57] and that many people will not be able to make use of eHealth technologies without at the same time being offered support in how to use the services [58].…”
Section: Discussionmentioning
confidence: 99%
“…One randomized trial of a mobile phone–based symptom-reporting system reported benefits to patients in the intervention group, 32 but another study 33 noted that their sample of 477 cancer patients preferred more “traditional” means of symptom reporting (e.g., paper, calling a nurse, in-person visit), compared with secure websites, text-messaging, or interactive voice response. Persistent challenges related to information-seeking include the credibility and trustworthiness of web-based information, and the uneven access to web-based resources among different subpopulations.…”
Section: Role Of Information Technology In Supporting Modern Cancer Carementioning
confidence: 99%
“…However, patient and professional preferences for face‐to‐face support (Kimman, Dellaert, Boersma, Lambin, & Dirksen, ) and resistance to adopt remote communication technologies (i.e. e‐mail, mobile phone text message and computer‐generated calls) (Kleiboer et al., ) highlight potential conflict regarding the best method of providing support for patients.…”
Section: Introductionmentioning
confidence: 99%